Structural Equation Modeling and Relationships Between Mental Wellbeing, Resilience and Self-stigma - Nordin, Mohamad Sahari (Sciedu Press, 2019)
This study investigated mental wellbeing of postgraduate and undergraduate students of International Islamic University Malaysia. Precisely, the objective of this study was to verify the validity of a proposed mental wellbeing model that include resilience and self-stigma exogenous variables, another aim of the survey was to determine if gender, education level, material status, international and non-international student and location where they live moderated the associations between mental wellbeing and its predictors. The survey adapted existing instruments: Warwick-Edinburgh Mental Well-being (WEMWB) Scale of 14-item questionnaire, Brief Resilience Scale of 6-item questionnaire and Self-Stigma of Seeking Help Scale (SSOSH) 10-item questionnaire and a demographic survey was developed for this study. The data were collected randomly from 315 student of International Islamic University Malaysia. To address the research objectives, the data were analyzed with confirmatory factor analysis and structural equation modeling. The results obtained by this study shows that, the model had an excellent fit, because RMSEA .007 < .06, CFI .999 > .95, Based on these results it can be concluded that the proposed model is valid, approving the very first hypothesis for this study. Additionally, gender, educational, location when they live and International and Malaysian student, did not moderate the predictor-mental wellbeing relationships.